THE ROLE OF DIDACTIC GAMES IN THE DEVELOPMENT OF STUDENTS' COGNITIVE ABILITIES (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The article includes various studies on the role of didactic games in the development of cognitive abilities. These games, in addition to learning and explaining certain topics, give students the opportunity to test themselves, solve problems, actively participate in the educational process and especially develop creativity.